Transitioning toward Sustainable Development Goals: The Role of Household Environment in Influencing Child Health in Sub-Saharan Africa and South Asia Using Recent Demographic Health Surveys - Anand, Ankit; Roy, Nobhojit (Frontiers in Public Health, 2016)
The millennium development goals are now replaced by seventeen sustainable development goals. The emphasis of old goals was on improving water, sanitation, and child mortality conditions in developing countries. The study explored the major question about the association between different household environment conditions with child survival and health in Sub-Saharan African and South Asian countries in the current scenario. This paper estimated the risk of death, morbidity and under-nutrition among children living in households with the improved sources of water, sanitation and non-solid cooking fuel. Two sources of information explored in this study. First, data from World Health Statistics (WHS) -2014 for all of the Sub-Saharan African and South Asian countries were used. Second, available standard Demographic and Health Survey performed in the countries of Sub-Saharan Africa and South Asia after 2010, included in the study. It resulted in inclusion of 15 countries which were Bangladesh (2011), Congo Republic (2013-14), Cote d'Ivoire (2011-12), Ethiopia (2011), Gambia (2013), Mali (2012-13), Mozambique (2011), Namibia (2013), Nepal (2011), Niger (2012), Nigeria (2013), Pakistan (2012-13), Sierra Leone (2013), Uganda (2011) and Zambia (2013). The Scatter plot diagram was plotted, and the curve was fitted using the WHS-2014. Cox regression and logistic regression were used to estimate adjusted risks (odds ratio) of child mortality and health outcomes using DHS surveys. The use of non-solid cooking fuel was very high in most of the Sub-Saharan African and South Asian Countries. There was a positive correlation between improving access to safe drinking water and sanitation. The exponential curve fitted well with child mortality and Household environmental indicators. The use of improved source of water and sanitation significantly related with the lower odds ratio of death, morbidity and under-nutrition among children aged 12-59 months. The risks were not significant for children aged less than 12 months. The study provides evidence that these environmental conditions hold importance for improving child health, especially in Sub-Saharan African countries.